A New Classification and Description of Shale Pore System: from the Burial History Perspective. Issue 1 (November 2020) - Zhao, Tianyi; Yin, Xia; Chen, Gang; Tian, Lingyu
Abstract: Accurate micro-storage and mechanism of shale gas is important for defining and describing the adsorption characteristics, and for gas-in-place estimation. In this paper, reservoir forming process is divided into early stage and late stage, and the initial gas-water distribution in different stage is redefined. Different from the widely used solid-gas interface adsorption theory, the pore system in original shale reservoir is divided into solid-gas system and solid-liquid-gas system. Gas pores existing in organic matters belong to solid-gas system, and are classified into residual gas pores and metamorphic gas pores. Plant tissue pores in organic and mineral pores belong to solid-liquid-gas system. Their characteristics are described.